Interleukin 6 as a marker of depression in women with sleep apnea. (25th March 2020) - Campos‐Rodriguez, Francisco; Cordero‐Guevara, Jose; Asensio‐Cruz, Maria Isabel; Sanchez‐Armengol, Angeles; Sanchez‐Lopez, Veronica; Arellano‐Orden, Elena; Gozal, David; Martinez‐Garcia, Miguel Angel
Abstract: Depression is common in women with obstructive sleep apnea (OSA), but objective markers of depression have not yet been explored in such patients. We hypothesized that inflammation and antioxidant biomarkers may be associated with depression in a cohort of OSA women. We conducted a multicentre, cross‐sectional study in 247 women diagnosed with moderate‐to‐severe OSA. Depression was assessed by the depression subscale of the Hospital Anxiety and Depression Questionnaire (HAD‐D) and defined as a score ≥11. Associations between tumour necrosis factor α (TNFα), interleukin 6 (IL‐6), C‐reactive protein (CRP), intercellular adhesion molecule 1 (ICAM‐1), catalase (CAT), superoxide dismutase (SOD) and brain‐derived neurotrophic factor (BDNF) plasma levels and depression were assessed. The women had a median (25th‐75th percentiles) age of 58 (51–65) years, body mass index (BMI) of 33.5 (29.0–38.3) Kg/m 2, Epworth Sleepiness Scale (ESS) score of 10 (6–13) and apnea–hypopnea index (AHI) of 33.3 (22.8–49.3). Logistic regression analyses revealed that only IL6 levels were associated with the presence of depression (adjusted odds ratio [OR], 1.20; 95% confidence interval [CI], 1.08–1.34), whereas linear regression further confirmed that IL6 levels were significantly associated with HAD‐D scores ( β = .154; 95% CI, 0.03–0.30). Multivariate regression analysis showed that IL6 (OR, 1.22; 95% CI, 1.09–1.36), ESS (OR, 1.10; 95% CI 1.02–1.19) and physical activity <30 min/day (OR, 2.51; 95% CI, 1.25–5.05) were independent predictors of depression. Thus, we conclude that in a cohort of women with moderate‐to‐severe OSA, IL6 levels are independently associated with the presence of depression and correlate with depression scores. Low physical activity and higher ESS scores are also independent indicators of risk of depression in this population.